2003
DOI: 10.1083/jcb.200301101
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of myocyte degeneration involving the Ca2+-permeable growth factor–regulated channel

Abstract: Disruption of the dystrophin–glycoprotein complex caused by genetic defects of dystrophin or sarcoglycans results in muscular dystrophy and/or cardiomyopathy in humans and animal models. However, the key early molecular events leading to myocyte degeneration remain elusive. Here, we observed that the growth factor–regulated channel (GRC), which belongs to the transient receptor potential channel family, is elevated in the sarcolemma of skeletal and/or cardiac muscle in dystrophic human patients and animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
218
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(230 citation statements)
references
References 49 publications
10
218
2
Order By: Relevance
“…42,50,51 The CsA treatment did not ameliorate the alteration of calcium homeostasis that is a typical hallmark of dystrophic fibers and is worsened by exercise. 2,4,29 CsA per se may even lead to a further increase in calcium mobilization; 52 thus our finding leads to two main considerations: the first one is that the alteration in calcium homeostasis is rather independent on the inflammatory reaction. The second is that CsA acts on the sensitive parameters independently or downstream the alteration of calcium homeostasis.…”
Section: Csa Exerts Different Effects On Functional Cellular Parametementioning
confidence: 74%
See 1 more Smart Citation
“…42,50,51 The CsA treatment did not ameliorate the alteration of calcium homeostasis that is a typical hallmark of dystrophic fibers and is worsened by exercise. 2,4,29 CsA per se may even lead to a further increase in calcium mobilization; 52 thus our finding leads to two main considerations: the first one is that the alteration in calcium homeostasis is rather independent on the inflammatory reaction. The second is that CsA acts on the sensitive parameters independently or downstream the alteration of calcium homeostasis.…”
Section: Csa Exerts Different Effects On Functional Cellular Parametementioning
confidence: 74%
“…This leads to a complex and still not fully understood network of interconnected pathogenic events responsible for progressive muscle degeneration; these events involve the increased entrance of calcium, the activation of proteases, and the occurrence of a functional ischemic state. [1][2][3][4] Recent evidence suggests that a chronic inflammatory state is a secondary reaction that strongly contributes to the progression of the pathology. A significant overexpression of inflammatory and immune response genes has been described by microarray in muscle of dystrophic subjects.…”
mentioning
confidence: 99%
“…Different reports have shown that heat above 52°C, hypo-osmolarity, membrane stretch or PI3-kinase regulated membrane insertion of the channel could be implicated in the regulation of TRPV2 activity [10,12,13,22]. However, some of these observations have proved difficult to reproduce.…”
Section: Discussionmentioning
confidence: 99%
“…Other TRPV2 activation mechanisms have also been proposed. In myocytes, TRPV2 channels behave as mechano-and osmo-gated channels and could be involved in the regulation of vascular tone or in myocyte degeneration [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the transient receptor potential vanilloid 2 (TRPV2) channel was noted in abundance in murine myocardial tissue, specifically in the left ventricle 14. Iwata et al initially described that cardiac‐specific overexpression of TRPV2 resulted in chamber dilation of all cavities of the murine heart,15 while our laboratory recently demonstrated increased expression of TRPV2 in diseased hearts 16. Related studies by our laboratory demonstrated that stimulation of the channel with probenecid in isolated cardiomyocytes resulted in increased cytosolic calcium concentrations with improved contractility and relaxation, independently of the β‐adrenergic signaling pathway 17.…”
Section: Introductionmentioning
confidence: 99%